2016
DOI: 10.1080/0886022x.2016.1209070
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in pediatric renal biopsies: analysis of pediatric renal biopsies in national nephrology registry data

Abstract: Renal biopsy is the gold standard method for determining the diagnosis, treatment, and prognosis in children with renal disease. This study aims to evaluate the histopathological features of pediatric renal biopsies obtained from the national nephrology registry in the last two decades. Data recorded in the Turkish Society of Nephrology Registry System (TSNRS) in 1991 as well as in between 2001 and 2010 were analyzed. A total of 3892 biopsies were recorded; with the least number in 1991 (total 103 biopsies fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
4
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 12 publications
3
12
4
5
Order By: Relevance
“…Our comparative study of PHD-s of all biopsies showed significant increase of IgAN from 13.8% in our previous study to 24.7% in this study [2]. Similar results were noticed in some other comparative studies as well [3,12]. Those findings might be the result of higher numbers of biopsied patients with isolated hematuria and changes in classification of IgAN.…”
Section: Trends Of Phd Results Along the Timesupporting
confidence: 91%
See 3 more Smart Citations
“…Our comparative study of PHD-s of all biopsies showed significant increase of IgAN from 13.8% in our previous study to 24.7% in this study [2]. Similar results were noticed in some other comparative studies as well [3,12]. Those findings might be the result of higher numbers of biopsied patients with isolated hematuria and changes in classification of IgAN.…”
Section: Trends Of Phd Results Along the Timesupporting
confidence: 91%
“…In accordance with the inclusion criteria, among the total number of patients with glomerular and tubulointerstitial diseases admitted to our Department during the investigated period, renal biopsy was performed in 23.4% of cases. Contrary to our results, the study by Fidan et al reported kidney biopsy in about 10% of patients with renal diseases [3]. This difference might be attributed to still unclear/different inclusion criteria.…”
Section: Indications For Renal Biopsycontrasting
confidence: 99%
See 2 more Smart Citations
“…Although a renal biopsy is difficult in children because of variable sizes of kidneys and different levels of cooperation, especially with the possibility of ultrasound-guided biopsy enhanced with the latest technologies, clinicians can make a choice about biopsies undoubtedly [2]. The main indications for a renal biopsy in children include persistent microscopic hematuria with or without proteinuria, recurrent gross hematuria, steroid-dependent and steroid resistant nephrotic syndrome (NS), distinction of nephrotic syndrome/nephritic syndrome, persistently low C3 in acute post-streptococcal GN, acute renal failure of unknown etiology, cyclosporine protocol biopsy, renal involvement in systemic lupus erythematosus (SLE) and lastly, staging of HSP nephritis [3][4][5]. Although macroscopic hematuria has been described as the most common complication, the biopsy protocols and instruments used are not same in many publications to determine the complications and rates [2,6,7].…”
Section: Introductionmentioning
confidence: 99%